Multidisciplinary Management of Alveolar, Functional, and Esthetic Preservation of Incisor With Failed Root Treatment: A Case Report - Jesús Manuel Sánchez-Beltrán (Wolters Kluwer Medknow Publications, 2024)
We aimed to describe the diagnosis and treatment of an upper right central incisor with an unfavorable prognosis. A 16-year-old man with a history of severe dentoalveolar trauma with avulsion and a failed attempt at endodontic treatment of apexification, dyschromia, and severe internal root resorption was treated. The psychosocial conditions of this pediatric patient played a role in choosing the option of maintaining the incisor for alveolar preservation to plan prosthetic replacement with an osseointegrated implant in adulthood.